Harassment towards Women in the Novel 'Perempuan yang Menangis kepada Bulan Hitam' by Dian Purnomo - Hilaria Heldiria Door; RM. Teguh Supriyanto,; Yusro Edy Nugroho (Universitas Negeri Semarang, 2024)
The novel